2007
DOI: 10.1007/s00128-007-9164-0
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Toxic Heavy Metals by Rice (Oryza sativa L.) Cultivated in the Agricultural Soil near Zhengzhou City, People’s Republic of China

Abstract: Higher accumulation of toxic heavy metals in rice grown in agricultural soil may lead to health disorder. A field experiment was carried out to investigate uptake and translocation of Cd, Cr, Pb, As, and Hg by different parts of rice plant in various irrigation regions. The results showed the rice grain contained significantly lower amounts of five metals than straw and root in all sampling sites. Rice root accumulated Cd, As, and Hg from the paddy soil. Moreover, the rice plant transported As very weakly, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(78 citation statements)
references
References 13 publications
3
68
3
4
Order By: Relevance
“…The concentration of Zn, Cd, Pb, Co and Ni did not show any significant difference in the low-and highrisk areas for EC. Several studies have reported the list of heavy metals in various crops such as rice [1,10,17]. Due to high application of chemical fertilizers and pesticides in rice farms, rice produced in this region can act as a main source of heavy metals [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The concentration of Zn, Cd, Pb, Co and Ni did not show any significant difference in the low-and highrisk areas for EC. Several studies have reported the list of heavy metals in various crops such as rice [1,10,17]. Due to high application of chemical fertilizers and pesticides in rice farms, rice produced in this region can act as a main source of heavy metals [18].…”
Section: Discussionmentioning
confidence: 99%
“…The main pathway of human exposure to heavy metals is intake via the soil-crop system [1]. Among heavy metals, cadmium (Cd), lead (Pb), arsenic and mercury are considered toxic to plants, humans and soil microbial population [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 -22 2014 they are valued as fertilizer. When applied to soil through irrigation, they are reported to increase the yield of sugar cane, rice, and wheat (Liu et al 2007). However, long-term use of industrial effl uents for irrigation may cause the concentrations of the trace metals Cd, Cu, Zn, Pb, and Mn to increase in surface soil, which may affect food quality and safety (Ibrahim et al 1998).…”
Section: Introductionmentioning
confidence: 99%